The Quality of Local Government Financial Statements and The Use of Financial Information in Decision Making - Raden Muhammad Rachmansyah Shadiqiawan; Sri Mulyani (Journal of Accounting Auditing and Business, 2020)
Financial statements contain information that is very helpful for users in making decisions. This study examines whether there are differences in the use of financial statement information decision making between the local government that obtain unqualified and qualified opinion for their financial statements. This study used the Mann Whitney test for hypothesis testing. Data was collected through a survey using a questionnaire on five local governments in West Java.The results of this study indicate that there are no significant differences in the use of financial statement information for local government decision-making, both in local governments that obtain unqualified and qualified opinions for their financial statements. This study also found that the financial statements most often used as a basis for decision making in the two groups of local governments are budget realization statement.